Analisis pola kemitraan usaha peternakan ayam pedaging sistem closed house di Plandaan Kabupaten Jombang - Nurul Azizah; Hari Dwi Utami; Bambang Ali Nugroho (Faculty of Animal Science, Universitas Brawijaya, 2013)
This research was conducted on the close house broiler farm owned by Mr. Nanang’s partnership with “Pesona Ternak Gemilang” Ltd at Plandaan subdistrict, Jombang Regency. The data were collected from 19th March to 19th April 2013. The purpose of this research was: 1) to investigate the broiler farm partnership pattern, 2) to determine the efficiency of broiler farm business. Descriptive analysis was carried out to analyze the rights as well as the obligations between the nucleus and the plasma. Also, the method was used to calculate the cost of production, revenues, profits and the R/C Ratio. The study shows that plasma has committed to the letter of treaty obligations in raising broiler. The first period of broiler farming using closed house system was found more efficient compared to other periods in which the production cost paid for 31,000 broilers was IDR. 615,554,603 or IDR. 19,857/bird and it could earn revenue about IDR. 740,397,545 or IDR. 27,225/bird. The profit per period was IDR.124,842,942 or IDR. 4,027.-/bird and the R/C ratio was 1.372. Keywords: nucleus and plasma partnership, broiler, R/C ratio